Sekolah Seni Lukis Di Kota Padang Dengan Pendekatan Arsitektur Kontemporer - Meike Syahlendra; Wahyu Hidayat; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Art Painting School with Contemporary Architecture Approach is a place to learn and understand art of painting so that it can be accepted and developed in the community. As with art of painting, contemporary architecture continues to grow over time. With the same characteristics, contemporary architecture can convey building functions properly. To be able to show the art of painting in thebuilding a transparent concept is applied with the aim of using it to be able to understand and learn painting directly. The research method used includes field data collection, literature study and empirical studies. The results of this study can design buildings that are good and in accordance with the functions and principles of Contemporary Architecture, namely a solid building, the concept of open space, suitability of outer and inner space, comfort and landscape exploration.Key Words: School, Painting, Transparent, Contemporary